Glacial‐Isostatic Adjustment Models Using Geodynamically Constrained 3D Earth Structures. (13th November 2021) - Bagge, M.; Klemann, V.; Steinberger, B.; Latinović, M.; Thomas, M.
Abstract: Glacial‐isostatic adjustment (GIA) is the key process controlling relative sea‐level (RSL) and paleo‐topography. The viscoelastic response of the solid Earth is controlled by its viscosity structure. Therefore, the appropriate choice of Earth structure for GIA models is still an important area of research in geodynamics. We construct 18 3D Earth structures that are derived from seismic tomography models and are geodynamically constrained. We consider uncertainties in 3D viscosity structures that arise from variations in the conversion from seismic velocity to temperature variations (factor r ) and radial viscosity profiles (RVP). We apply these Earth models to a 3D GIA model, VILMA, to investigate the influence of such structure on RSL predictions. The variabilities in 3D Earth structures and RSL predictions are investigated for globally distributed sites and applied for comparisons with regional 1D models for ice center (North America, Antarctica) and peripheral regions (Central Oregon Coast, San Jorge Gulf). The results from 1D and 3D models reveal substantial influence of lateral viscosity variations on RSL. Depending on time and location, the influence of factor r and/or RVP can be reverse, for example, the same RVP causes lowest RSL in Churchill and largest RSL in Oregon. Regional 1D models representing the structure beneath the ice and 3D models show similar influence of factor r and RVP on RSL prediction. This is not the case for regional 1D models representing the structure beneath peripheral regions indicating the dependence on the 3D Earth structure. The 3D Earth structures of this study are made available. Plain Language Summary: Around 21, 000 years ago, sea level was 130 m below present‐day and large ice sheets with thicknesses of several kilometers were covering parts of North America and northern Europe. The response of the solid Earth due to ice‐sheet loading is called the glacial‐isostatic adjustment (GIA) and has caused subsidence of several hundreds of meters below ice sheets. The deformation behavior depends on the structure of the Earth's interior from the crust to the mantle. From seismic waves, we gain insight into the 3D Earth structure that varies laterally and with depth. However, there are still many unknowns characterizing feasible Earth structures. Therefore, the consideration of geodynamic and geological constraints is particularly essential, for example, for the validation of GIA models. Here, we use GIA models and implement an ensemble of geodynamically constrained 3D Earth structures, as well as Earth structures which vary with depth alone (1D), to simulate the sea level over the last 120, 000 years. We investigate how uncertainties in the 3D Earth structure influence the predicted RSL variability. Key Points: We create an ensemble of geodynamically constrained 3D Earth structures that vary in conversion from seismic tomography models to viscosity We predict the relative sea‐level over the last deglaciation period and investigate the effect of 3D Earth structure variations We observe variability in the response which cannot be reproduced by applying regionally adapted 1D Earth models